2005
DOI: 10.1080/02699200500085426
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning from analog to digital audio recording in childhood speech sound disorders

Abstract: Few empirical findings or technical guidelines are available on the current transition from analog to digital audio recording in childhood speech sound disorders. Of particular concern in the present context was whether a transition from analog-to digital-based transcription and coding of prosody and voice features might require re-standardizing a reference database for research in childhood speech sound disorders. Two research transcribers with different levels of experience glossed, transcribed, and prosody-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…With the exception of the latter finding, the remaining agreement percentages, ranging from low 70% values to high 90% values, are as high or higher than transcription reliability findings reported in prior reviews of the literature and in our laboratory (McSweeny & Shriberg; 1995, Shriberg & Lof; 1991, Shriberg et al, 2005). Following is a summary of trends in the individual and mean agreement estimates shown in figure 3.…”
Section: Resultscontrasting
confidence: 53%
“…With the exception of the latter finding, the remaining agreement percentages, ranging from low 70% values to high 90% values, are as high or higher than transcription reliability findings reported in prior reviews of the literature and in our laboratory (McSweeny & Shriberg; 1995, Shriberg & Lof; 1991, Shriberg et al, 2005). Following is a summary of trends in the individual and mean agreement estimates shown in figure 3.…”
Section: Resultscontrasting
confidence: 53%
“…Studying the raw data in detail revealed how there appeared to be a considerable difference in the coding of palatalization. Listener 1 usually categorized this as a cleft speech characteristic, in contrast to Listener 2 who categorized this more typically as a non‐cleft speech immaturity . This may be because the category non‐cleft speech immaturities was not given sufficient emphasis in training .…”
Section: Discussionmentioning
confidence: 97%
“…Shriberg et al. compared digital and analogue audio recording systems and noted a trend for the digital samples to be scored more critically compared to the analogue samples. This suggests the improved speech results are not associated with the nature of the recording medium.…”
Section: Discussionmentioning
confidence: 99%
“…The transcripts were formatted so that analysis could be carried out using the previously described SDCS (Shriberg et al, 1997b). Transcription agreement estimates for the samples and transcribers used in the current study are reported elsewhere (Shriberg & Lof, 1991;McSweeny & Shriberg, 1995;Shriberg et al, 2005).…”
Section: Transcription and Analysismentioning
confidence: 99%